Complications of extraction socket among diabetic, hypertensive and smokers in comparison to normal patients - Farhan Raza Khan; Komal Iftikhar; Ayesha Hashmi; Madiha Ismail; Sheharyar Hameed Siddiqui; Humayun Kaleem Siddiqui (Elsevier, 2021)
Background: Tooth extraction is a common oral surgery procedure carried out mainly on outpatient basis. It is important to evaluate the risk factors which can lead to various complications after extraction of teeth. Normal healing of an extraction socket may be impaired by the presence of one or more factors. The objective of this study was to find out the effect of the medical conditions such diabetes, hypertension and smoking habit on the process of normal healing following dental extractions. Methodology: Patients reported for dental extraction in oral and maxillofacial surgery department at Baqai Dental College were divided into two groups. A control group and a disease group with systemic conditions like diabetes mellitus, hypertension and habit of smoking. All the extractions were performed under local anesthesia by the dental officers. SPSS version 17 was used to perform statistical analysis to identify the risk factors and possible relationships with the healing in extraction sockets. Results: In this study 88 females, 152 males participated. In healthy group there were 93 patients enrolled. In the healthy subjects (n = 93) 39.7% reported complications whereas in the diseased group (n = 147) the reported complications were 61.2% (Table 1). The percentages and number of patients are charted below according to complications. Table 2 is showing different complications and their percentages. Table 3 is showing disease patterns in both the groups and odds ratio which is greater than 4 in our study. Conclusions: The odds of complications among subjects with co-morbidities are four times that of same in the healthy subjects.